1995
DOI: 10.1177/004051759506500601
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Greystate Fabrics as a Function of Yarn Structure

Abstract: Data analysis of the compression of a fabric can only be done using a mathematical model to smooth the results. The best formula is Van Wyk's, although the meaning of the physical parameters is very difficult to define for a fabric. On the basis of Van Wyck's equation, a study of the compressibility of a fabric whose weft is made of multiple threads (classic ply-yams, open-end, combed or carded) shows that the struc ture of a fabric has a higher value than the structure of a thread. The mechanical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…However, this simplification seems to be convenient for high pressures [15] but not in other cases [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, this simplification seems to be convenient for high pressures [15] but not in other cases [23].…”
Section: Introductionmentioning
confidence: 99%
“…Van Wyk [24] proposed an appropriate function to fit measurement data of a fibrous material during compression. Later this empirical function has been applied to the case of standard fabrics [25] and hairy fabrics [26,27]. On this basis the following expression can be derived for the indentation pressure, i.e.…”
Section: Brush Model For the Friction Force Due To Deformationmentioning
confidence: 99%
“…At present, tubular fabrics are more concentrated on the tracheal stent [3,4], the mechanical properties of the tubular fabric and so on [5,6]. Many researchers studied the compression property about woven fabric [7][8][9][10], nonwoven fabrics [11], and knitted fabrics [12][13][14][15][16][17][18]. Though the structures of fabrics are different, the key of these fabrics is the compression properties.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers presented the basic compression theory for fiber assembly fabrics, which aimed to observe how the structure of a yarn or a fabric influenced its compressibility before finishing [8,19,20]. They found that the curve of compression was independent of the fiber arrangement when a yarn was made.…”
Section: Introductionmentioning
confidence: 99%